Pelatihan Microsoft Excel Dasar untuk Meningkatkan Keterampilan Administrasi Guru dan Wali Santri - Baginda Oloan Lubis; Firstianty Wahyuhening Fibriany; Eri Riana; Santoso Setiawan (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Administrative management and financial record-keeping in non-formal educational institutions such as Taman Pendidikan Al-Qur'an (TPQ) are still predominantly performed manually, resulting in various challenges, including difficulties in data retrieval, a high risk of data loss, low accuracy, and inefficient workflows. Similar issues were identified at TPQ Bina Ummah, where teachers and administrative staff had limited proficiency in using Microsoft Excel for administrative management and recording cash inflows and outflows. Consequently, data recapitulation was time-consuming and prone to calculation errors. This community service program aimed to improve the participants' competency in using Microsoft Excel to support more effective and accurate administrative management. The implementation method consisted of needs assessment, development of training modules, hands-on workshops, practical mentoring, and evaluation through pre-test and post-test assessments. The training focused on four core competencies: creating tables, using the SUM and AVERAGE functions, applying the Sort and Filter features, and configuring document print settings. The activity was conducted offline on May 9, 2026, and attended by 20 participants, consisting of teachers and administrative staff of TPQ Bina Ummah. The evaluation results showed that the average pre-test score increased from 45.5 to 82.0 in the post-test, representing an improvement of 36.5 points (approximately 80.2% compared with the initial score). Furthermore, 90% of the participants were able to independently prepare cash receipt and cash disbursement reports using Microsoft Excel based on the case studies provided. These findings indicate that the training successfully enhanced participants' competencies in administrative management while strengthening their digital literacy to support more professional, effective, and accountable administrative governance within the TPQ.